Analysis of Job Satisfaction and Workload on the Productivity of Executive Nurses at Samaritan Hospital, Palu - Gaury, Andi; Adda, Harnida Wahyuni; Rossanty, Ni Luh Putu Evvy; Lamusa, Faruq (PT. Global World Scientific, 2024)
This research aims to determine the effect of job satisfaction and workload on the productivity of implementing nurses at Samaritan Hospital, Palu City. The research method used in this research uses quantitative descriptive method analysis, with the number of samples used in the research being 30 respondents. The analysis technique used in this research is multiple linear regression analysis with the help of SPSS 25 software. The sampling technique used is simple random sampling, where samples are taken from the population randomly without paying attention to the strata of the population. The results of hypothesis testing show that job satisfaction and workload simultaneously significantly affect nurse productivity, job satisfaction partially affects nurse productivity, and workload partially affects nurse productivity at Samaritan Hospital in Palu.